Monte Carlo simulation of magnetic properties of a nano-graphene bilayer in a longitudinal magnetic field - Wang, Wei; Liu, Ruijia; Lv, Dan; Luo, Xiaohong (Superlattices and microstructures, 2016)
Monte Carlo simulation has been used to study the magnetic properties of a nano-graphene bilayer which consists of the upper layer A with spin-3/2 and the bottom layer B with spin-5/2. The effects of the single-ion anisotropy, the intralayer exchange coupling and the longitudinal magnetic field on the magnetization, the susceptibility, the blocking temperature and hysteresis loops of the mixed-spin nano-graphene bilayer system have been examined detailedly. In particular, the variations of the blocking temperature with different intralayer exchange couplings, single-ion anisotropies, and the longitudinal magnetic field are obtained for the present system. Many multiple hysteresis loop behaviors have also been found, depending on the combinations of both the upper and bottom layer magnetizations in the longitudinal magnetic field. Through a comparison, our results obtained are according well with other theoretical researches and experimental results. •A mixed-spin Ising model has been proposed to describe a nano-graphene bilayer.•Theoretical results for magnetizations and susceptibilities of a nano-graphene bilayer were presented.•The effects of exchange couplings, anisotropies and the longitudinal magnetic field on the blocking temperature are studied.•Many multiple hysteresis loops have been found in a certain parameter range.